Speakers’ Attitudes Toward the Normative Pronunciation of Certain Words with a (Predominantly) Long Falling Accent on the Medial Syllable in Practice - Ivaniš, Jovana V.; Čopa, Miljana B. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The subject of this research is the attitudes of Serbian language speakers toward the normative pronunciation of certain loanwords that, in practice, most commonly bear a long falling accent on the medial syllable (e.g., ambаsаdor, radijаtor, telèvizija, etc.). The aim of the study is to explore how speakers perceive this segment of the accentual norm of standard Serbian and to what extent they find it acceptable. The corpus was collected using a questionnaire specifically designed for the purposes of this research, which included audio recordings of the aforementioned types of words, pronounced according to the normative rules of standard Serbian. These examples were excerpted from various television programs, and participants were asked to evaluate the recordings based on specific criteria: correctness, normativity, neutrality, naturalness, aesthetic appeal, and prestige of pronunciation. Participants were also given the opportunity to explain their responses. The results obtained were subjected to quantitative analysis to determine whether the evaluative judgments of speakers from various dialectal regions differ. We also examined whether factors such as gender and education level correlate with participants’ attitudes toward the phenomenon under study. Furthermore, we relate these findings to the first part of the research, which focused on the normative pronunciation of certain words that, in practice, most commonly feature a short falling accent on the final syllable. The results of the study may serve as a guideline for considering potential directions for adapting the accentual norm.
Keywords: attitudes; accentual norm; usage norm; standard Serbian; public discourse